PENERAPAN UPAH MINIMUM PROPINSI (UMP) DARI DINAS TENAGA KERJA PROVINSI SUMATERA UTARA TERHADAP PERUSAHAAN-PERUSAHAAN SWASTA - Parlindungan Marpaung; Madin Silalahi; Paskah Wirawan Daeli (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UDA, 2019)
This study aims at finding out how the application of the provincial minimum wage (UMP) from labor offices the North Sumatra province toward private companies in North Sumatra, obstacles in applying minimum wages and solutions to overcome problems in applying minimum wages. Then, concept of procedures for conducting research was discussed. Research method used is qualitative method meanwhile data collection technique was done by having interview with informants for getting accurate information and data. There are 6 informants. The results of this study are that the application of the provincial minimum wage (UMP) taking into accounts the results of a decent living needs survey (KHL) obtained from the results of a market survey to get results that will be submitted to the governor setting the provincial and district minimum wage levels.